Characterisation of oligosaccharides from Drosophila melanogaster glycoproteins - Williams, Phillip J.; Wormald, Mark R.; Dwek, Raymond A.; Rademacher, Thomas W.; Parker, George F.; Roberts, David R. (Biochimica et biophysica acta, 1991)
An analysis of the released oligosaccharides from a membrane glycoprotein preparation of third instar larvae (3rdIL), and purified larval serum protein 2 (LSP2) from Drosophila melanogaster was performed. Sequential exoglycosidase digestion in combination with high-resolution gel permeation chromatography and partial acetolysis indicated the presence of two series of oligomannosides; one of these series was unusual and characterized by the presence of a core α1–6 linked fucose, the other was a typical mammalian oligomannose series containing the following isomers −D 1, −D 2, −D 12, −D 123 and −CD 123 as well as the unprocessed Man 9GlcNAc 2 structure. Conventional oligomannose could only be detected in the LSP2 sample. This study opens the way to use powerful molecular and classical genetic techniques to analyse the control and functional significance of glycosylation in higher organisms.